Navigating the meta-crisis of generativity: adapting qualitative research quality criteria in the era of generative AI - Dahal, Niroj; Hasan, Md. Kamrul; Ounissi, Amine; Haque, Md. Nurul; Kapar, Hiralal (Frontiers in Research Metrics and Analytics, 2025)
Integrating generative AI (GenAI) in qualitative research offers innovation but intensifies core epistemological, ontological, and ethical challenges. This article conceptualizes the meta-crisis of generativity—a convergence of Denzin and Lincoln's three crises: representation (blurring human/AI authorship), legitimation (questioning trust in AI-generated claims), and praxis (ambiguity in non-human participation). We examine how human-GenAI collaboration challenges researchers' voice, knowledge validity, and ethical agency across research paradigms. To navigate this, we propose strategic approaches: preserving positionality via voice annotation and reflexive bracketing (representation); ensuring trustworthiness through algorithmic audits and adapted validity checklists (legitimation); and redefining agency via participatory transparency and posthuman ethics (praxis). Synthesizing these, we expand qualitative rigor criteria—such as credibility and reflexivity—into collaborative frameworks that emphasize algorithmic accountability. The meta-crisis is thus an invitation to reanimate the critical ethos of qualitative research through interdisciplinary collaboration, balancing the potential of GenAI with ethical accountability while preserving humanistic foundations.